Hazelnut shell-based porous adsorption carbon material as well as preparation method and application thereof

Through the preparation of hazelnut shell-based porous adsorption carbon materials, the existing porous carbon has been solved, with low specific surface, poor adsorption performance and poor circulation stability, and efficient removal of pollutants in waste water and resource utilization of waste biomass.

CN119897063APending Publication Date: 2025-04-29XUZHOU JINLONG HUPAN SEMICONDUCTOR MATERIALS RESEARCH CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411941495.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing porous carbon has problems such as lower specific surfaces, poor adsorption performance, poor circulation stability and complex preparation processes, making it difficult to effectively remove pollutants in water bodies.

Method used

Using hazelnut shell as raw material, hazelnut shell-based porous adsorption carbon material with high specific surface area, high hardness, high pore volume, excellent adsorption performance and excellent cycle stability is prepared through pyrolysis carbonization, activation of pore formation and pickling.

Benefits of technology

It has achieved efficient removal of textile sewage, papermaking sewage or dye sewage, and the preparation method of materials is simple, convenient for industrial production, and resource utilization of waste biomass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119897063A_ABST
    Figure CN119897063A_ABST
Patent Text Reader

Abstract

The invention discloses a hazelnut shell-based porous adsorption carbon material as well as a preparation method and application thereof, and the method for preparing the hazelnut shell-based porous adsorption carbon material comprises the following steps: carrying out pyrolysis carbonization on hazelnut shells to obtain hazelnut shell carbon; grinding and mixing the hazelnut shell carbon and an activating agent, and activating and pore-forming; and performing acid pickling, water washing and drying on the activated and pore-formed material to obtain the hazelnut shell-based porous carbon material. The hazelnut shell is used as a raw material, and the hazelnut shell-based porous adsorption carbon material with high specific surface area, high hardness, high pore volume, excellent adsorption performance and excellent cycle stability is prepared through an alkali activation process by combining the characteristics of high hardness and rich alkali metal and alkaline earth metal of the hazelnut shell; the method can be effectively applied to treatment of textile wastewater, papermaking wastewater or dye wastewater and the like, pollutants can be removed, resource utilization of waste biomass can be achieved, and the development concept of treating pollution with waste is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of waste biomass resource utilization, and specifically, to a hazelnut shell-based porous adsorption carbon material and a preparation method and application thereof. Background Art

[0002] With the continuous rise of industries such as textiles, papermaking, and dye synthesis, the discharge of dye pollutants in water is increasing, exacerbating the problem of water pollution, so sewage treatment needs to be solved urgently. Porous carbon adsorption to remove water pollutants has become a research hotspot due to its convenient operation and low cost. However, existing porous carbon has problems such as low specific surface area, poor adsorption performance, poor cycle stability, and complex preparation process. Summary of the invention

[0003] The present application aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the purpose of the present application is to propose a hazelnut shell-based porous adsorption carbon material and its preparation method and application. The present application uses hazelnut shell as a raw material, combined with its high hardness and rich in alkali metals and alkaline earth metals, through an alkali activation process, to prepare a hazelnut shell-based porous adsorption carbon material with high specific surface area, high hardness, high pore volume, excellent adsorption performance, and excellent cyclic stability. It can be effectively used in the treatment of textile wastewater, papermaking wastewater or dye wastewater, etc., which can not only complete the removal of pollutants, but also achieve the resource utilization of waste biomass, realizing the development concept of "using waste to treat pollution".

[0004] In a first aspect of the present application, a method for preparing a hazelnut shell-based porous adsorbent carbon material is proposed. According to an embodiment of the present application, the method comprises:

[0005] Pyrolysis and carbonization of hazelnut shells are performed to obtain hazelnut shell carbon;

[0006] Grinding and mixing the hazelnut shell carbon and an activating agent to activate and form pores;

[0007] The activated and pore-forming material is acid-washed, water-washed and dried to obtain a hazelnut shell-based porous carbon material.

[0008] According to the method for preparing the hazelnut shell-based porous adsorption carbon material in the above embodiment of the present application, the present application uses hazelnut shell as raw material, combined with its high hardness and rich alkali metal and alkaline earth metal characteristics, through the alkali activation process, to prepare a hazelnut shell-based porous adsorption carbon material with high specific surface area, high hardness, high pore volume, excellent adsorption performance, and excellent cycle stability, which can be effectively used in the treatment of textile wastewater, papermaking wastewater or dye wastewater, etc., which can not only complete the removal of pollutants, but also achieve the resource utilization of waste biomass, and realize the development concept of "using waste to treat pollution". In addition, the preparation method of the present application is simple, which is conducive to large-scale industrial production.

[0009] In addition, the method for preparing the hazelnut shell-based porous adsorbent carbon material according to the above embodiment of the present application may also have the following additional technical features:

[0010] In some embodiments of the present application, before pyrolyzing and carbonizing the hazelnut shell, the method further comprises: washing the hazelnut shell, drying it, and performing a first crushing;

[0011] Optionally, washing the hazelnut shells with deionized water 3 to 5 times;

[0012] Optionally, the average particle size of the hazelnut shells after the first crushing is 1 mm to 4 mm.

[0013] In some embodiments of the present application, the hazelnut shell is pyrolyzed and carbonized under an inert atmosphere; and / or the temperature for pyrolyzing and carbonizing the hazelnut shell is 550° C. to 700° C., and the time is 30 min to 3 h.

[0014] In some embodiments of the present application, before grinding and mixing the hazelnut shell carbon and the activating agent, the method further comprises: performing a second crushing on the hazelnut shell carbon;

[0015] Optionally, the particle size of the crushed hazelnut shell carbon is no more than 125 μm.

[0016] In some embodiments of the present application, the hazelnut shell carbon is activated and pore-formed under an inert atmosphere; and / or the activator includes at least one of potassium hydroxide, sodium hydroxide, zinc chloride and potassium carbonate; and / or the mass ratio of the hazelnut shell carbon to the activator is 1:(1-3); and / or the temperature of the activation pore-formation is 600°C-800°C, and the time is 30min-70min.

[0017] In some embodiments of the present application, the activated pore-forming material is pickled with an acid solution; and / or the pickling time is 4 hours to 6 hours; and / or the water washing is performed until the pH of the washing solution is 7.

[0018] In some embodiments of the present application, the acid solution includes at least one of hydrochloric acid and nitric acid; and / or the concentration of the acid solution is 1 mol / L to 3 mol / L.

[0019] In the second aspect of the present application, a hazelnut shell-based porous adsorbent carbon material is proposed, and the hazelnut shell-based porous adsorbent carbon material is prepared by the method of the first aspect. As a result, the hazelnut shell-based porous adsorbent carbon material has a high specific surface area, high strength, and high pore volume, thereby effectively improving the adsorption performance and cyclic stability of the hazelnut shell-based porous adsorbent carbon material, so that the hazelnut shell-based porous adsorbent carbon material can be effectively used in the treatment of textile wastewater, papermaking wastewater or dye wastewater, especially in the treatment of methylene blue wastewater, to complete the removal of pollutants in wastewater.

[0020] In addition, the hazelnut shell-based porous adsorption carbon material according to the above embodiment of the present application may also have the following additional technical features:

[0021] In some embodiments of the present application, the specific surface area of ​​the hazelnut shell-based porous adsorbent carbon material is not less than 1000 m 2 / g, preferably 1300m 2 / g~3200m 2 / g; and / or, the pore volume of the hazelnut shell-based porous adsorbent carbon material is not less than 0.5cm 3 / g, preferably 0.5cm 3 / g~1.5cm 3 / g; and / or, the micropore volume of the hazelnut shell-based porous adsorbent carbon material is not less than 0.5cm 3 / g, preferably 0.5cm 3 / g~1.2cm 3 / g; and / or, the average pore size of the hazelnut shell-based porous adsorbent carbon material is not less than 1.5nm, preferably 1.5nm to 2.1nm.

[0022] In the third aspect of the present application, a hazelnut shell-based porous adsorbent carbon material prepared by the method described in the first aspect or the hazelnut shell-based porous adsorbent carbon material described in the second aspect is proposed for use in treating sewage. Thus, the hazelnut shell-based porous adsorbent carbon material can be effectively used in the treatment of textile sewage, papermaking sewage or dye sewage, and is particularly used in the treatment of methylene blue sewage to remove pollutants in sewage.

[0023] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0025] Figure 1is a schematic flow chart of a method for preparing a hazelnut shell-based porous adsorption carbon material according to some embodiments of the present application;

[0026] Figure 2 The adsorption isotherm diagram of the hazelnut shell-based porous adsorption carbon material prepared in Examples 1 to 9 of the present application;

[0027] Figure 3 The pore volume and pore size distribution diagram of the hazelnut shell-based porous adsorption carbon material prepared in Examples 1 to 9 of the present application;

[0028] Figure 4 This is an electron microscope image of the untreated hazelnut shell raw material of Example 9 in the present application;

[0029] Figure 5 This is a scanning electron microscope image of the hazelnut shell-based porous adsorption carbon material prepared in Example 9 of the present application;

[0030] Figure 6 This is a transmission electron micrograph of the hazelnut shell-based porous adsorption carbon material prepared in Example 9 of the present application;

[0031] Figure 7 This is the adsorption graph of methylene blue by the hazelnut shell-based porous adsorption carbon material prepared in Examples 1 to 13 of the present application.

[0032] Figure 8 This is a cyclic stability diagram of the adsorption of methylene blue solution by the hazelnut shell-based porous adsorption carbon material prepared in Example 9 of the present application. DETAILED DESCRIPTION

[0033] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, and should not be construed as limiting the present application.

[0034] In the description of the present application, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred elements must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present application.

[0035] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0036] In this application, unless otherwise clearly specified and limited, the terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0037] In the present application, unless otherwise clearly specified and limited, a first feature being “above” or “below” a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being “above”, “above”, and “above” a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being “below”, “below”, and “below” a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.

[0038] This application is proposed by the inventor based on the following issues:

[0039] Hazelnut shells are biomass fruit shell waste with huge output. At present, most hazelnut shells are directly landfilled or incinerated, causing serious environmental pollution and waste of resources. The inventors found that hazelnut shells are rich in carbon content, low in ash content, high in hardness, high in alkali metal (Na and K) and alkaline earth metal (Mg and Ca, etc.) element content, and have the natural pore structure of biomass, which has the natural advantage of preparing high-strength, high specific surface area and large pore volume porous carbon.

[0040] In view of this, in order to solve the problem of environmental pollution and waste of resources caused by waste hazelnut shells, in the first aspect of the present application, a method for preparing a hazelnut shell-based porous carbon material with simple process, low cost and high adsorption capacity is proposed. Figure 1The method comprises: pyrolyzing and carbonizing hazelnut shells to obtain hazelnut shell carbon; grinding and mixing the hazelnut shell carbon with an activating agent to perform activation and pore formation; acid washing, water washing, and drying the activated and pore-forming material to obtain a hazelnut shell-based porous carbon material.

[0041] The beneficial effects that can be achieved by the method for preparing the hazelnut shell-based porous adsorbent carbon material proposed in this application are described in detail below:

[0042] The present application first pyrolyzes and carbonizes the hazelnut shell to remove the volatile matter and water in the hazelnut shell, and increases the carbon content, thereby obtaining hazelnut shell carbon with a high carbon content; at the same time, during the pyrolysis and carbonization process, the release of volatile matter helps to form a porous structure, thereby further improving the adsorption performance of the hazelnut shell-based carbon material obtained in the subsequent steps, making it more suitable for applications such as wastewater treatment. The hazelnut shell carbon is then activated and pore-formed with an activator. The activated and pore-formed material is then pickled to neutralize the alkaline activator remaining in the activation process; at the same time, during the pickling process, the metal element formed by the activator in the process of participating in the activation reaction can be washed away to retain the microporous structure, and the reactants formed by the alkali metal and alkaline earth metal in the process of participating in the activation reaction can be washed away to form a microporous structure, thereby further improving the specific surface area and porosity of the hazelnut shell-based porous carbon material.

[0043] Therefore, in view of the problems of low specific surface area, poor adsorption and decontamination performance, and poor cyclic stability of porous carbon in the prior art, the present application uses hazelnut shell as raw material, combined with its high hardness and rich in alkali metals and alkaline earth metals, and prepares hazelnut shell-based porous adsorption carbon materials with high specific surface area, high hardness, high pore volume, excellent adsorption performance, and excellent cyclic stability through an alkali activation process, which can be effectively applied to the treatment of textile wastewater, papermaking wastewater, or dye wastewater, etc., which can not only complete the removal of pollutants, but also achieve the resource utilization of waste biomass, and realize the development concept of "using waste to treat pollution". In addition, the preparation method of the present application is simple, which is conducive to large-scale industrial production.

[0044] Specifically, refer to the attached Figure 1 , the above method comprises:

[0045] S100: pyrolyzing and carbonizing the hazelnut shell to obtain hazelnut shell carbon;

[0046] In this step, the hazelnut shells can be pyrolyzed and carbonized under an inert atmosphere (such as a nitrogen atmosphere, an argon atmosphere, etc.) to remove volatiles and water in the hazelnut shells, increase the carbon content, and thus obtain hazelnut shell carbon with a high carbon content. At the same time, during the pyrolysis and carbonization process, the release of volatiles helps to form a porous structure, which can further improve the adsorption properties of the hazelnut shell-based carbon material obtained in the subsequent steps, making it more suitable for applications such as wastewater treatment. Further, the hazelnut shells can be pyrolyzed and carbonized in a muffle furnace.

[0047] According to some specific embodiments of the present application, the temperature for pyrolysis carbonization of hazelnut shells is 550°C to 700°C (for example, 550°C, 580°C, 600°C, 630°C, 650°C, 680°C, 700°C, etc.), and the time is 30min to 3h (for example, 30min, 1h, 1.5h, 2h, 2.5h, 3h, etc.). By limiting the temperature and time of pyrolysis carbonization within the above range, it is possible to further ensure the removal of volatiles and moisture in the hazelnut shells, increase the carbon content, and further obtain hazelnut shell carbon with a high carbon content.

[0048] Furthermore, the heating rate for pyrolysis and carbonization of hazelnut shells is not particularly limited. As some preferred embodiments, the heating rate may be 5° C. / min to 10° C. / min.

[0049] According to some further specific embodiments of the present application, before pyrolyzing and carbonizing the hazelnut shells, the method further includes: collecting discarded hazelnut shells, washing the hazelnut shells to remove dust and other impurities on the surface of the hazelnut shells, drying, and performing a first crushing.

[0050] As some specific embodiments, the hazelnut shells may be cleaned with deionized water for 3 to 5 times to ensure that dust and other impurities on the surface of the hazelnut shells are completely removed.

[0051] As some further specific embodiments, a constant temperature blast drying oven may be used for drying. Furthermore, the temperature of the constant temperature blast drying oven may be 80° C. to 120° C., and the drying time may be 8 h to 24 h.

[0052] As some further specific embodiments, the average particle size of the hazelnut shells after the first crushing may be 1 mm to 4 mm.

[0053] S200: grinding and mixing the hazelnut shell carbon and the activating agent, activating and forming pores, and obtaining a hazelnut shell-based porous carbon material;

[0054] In this step, the hazelnut shell carbon and the activator can be ground and mixed under an inert atmosphere, and activated to form pores to obtain the hazelnut shell-based porous carbon material. Furthermore, the activation and pore formation can be carried out in a tubular furnace.

[0055] In the embodiments of the present application, the reaction mechanism of using an activator to activate and form pores in the above hazelnut shell carbon is extremely complex, and the following is an example using potassium hydroxide (KOH) as the activator:

[0056] The carbon element in hazelnut shell carbon will react with KOH to generate K, H2 and K2CO3, which will consume the surface of hazelnut shell carbon and part of the internal carbon skeleton to form a grid-like carbon structure. At the same time, the generated potassium compounds and other by-products (H2O and CO2) will further react with carbon at high temperature to promote the development of the pore structure. In addition, the metallic potassium precipitated during the reaction process can be inserted into the carbon lattice on the surface and internal cavity of the carbon structure, causing the carbon lattice to expand, and after subsequent acid washing treatment, the metallic potassium will be washed away to retain the microporous structure, thereby obtaining a hazelnut shell-based porous carbon material with high specific surface area, high strength, large adsorption capacity, fast adsorption rate and good cyclic stability. The reaction equations involved are as follows:

[0057] KOH+C→K+H2+K2CO3;

[0058] K2CO3→K2O+CO2;

[0059] K2CO3→K2O+CO;

[0060] K2O+C→K+CO;

[0061] K+CO2→K2O+CO;

[0062] KOH → K2O + H2O;

[0063] C+H2O→CO+H2;

[0064] CO+H2O→CO2+H2;

[0065] CO2+K2O→K2CO3;

[0066] C+CO2→CO.

[0067] In addition, hazelnut shell carbon contains high levels of alkali metals (such as Na and K) and alkaline earth metals (such as Mg and Ca, etc.), which participate in the activation reaction during the activation pore-forming process, and then wash away the reactants during the subsequent acid washing process to form a microporous structure, thereby further improving the specific surface area and porosity of the hazelnut shell-based porous carbon material.

[0068] The inventors compared and analyzed the types and contents of trace metal elements in hazelnut shells, hazelnut shell carbon and other biomass / biomass carbon by X-ray fluorescence analysis (XRF). Table 1 shows the oxide content results of hazelnut shells, hazelnut shell carbon and other biomass / biomass carbon tested by X-ray fluorescence spectroscopy (XRF).

[0069] As can be seen from Table 1, in the ash component oxide composition of hazelnut shell carbon, the contents of CaO, K2O and MgO are relatively high, accounting for 34.86%, 31.66% and 10.18% respectively. This shows that the ash components of hazelnut shell carbon are mainly alkali metals and alkaline earth metals. By comparing the chemical composition of the ash components of other biomass / biomass carbons (such as corn cob carbon (CC), rice husk (RH), rapeseed stalks (RR) and peanut shells (PS), etc.), it is found that the content of alkali metals and alkaline earth metals in other biomass / biomass carbons is significantly lower than that of hazelnut shells. Therefore, the content of elements such as K, Ca and Mg in hazelnut shells is relatively high. According to this characteristic, it is conducive to the preparation of porous carbon with a large specific surface area.

[0070] Table 1 Chemical composition of ash from hazelnut shells, hazelnut shell charcoal and other biomass

[0071]

[0072] In the embodiments of the present application, the specific type of the above-mentioned activator is not particularly limited. As some preferred embodiments, the above-mentioned activator includes at least one of potassium hydroxide (KOH), sodium hydroxide, zinc chloride and potassium carbonate, and potassium hydroxide (KOH) is more preferred.

[0073] According to some specific embodiments of the present application, the mass ratio of the hazelnut shell carbon to the activator is 1:(1-3), for example, it can be 1:1, 1:2, 1:3, etc. Therefore, by limiting the mass ratio of hazelnut shell carbon to the activator within the above range, it can be further ensured that the activator effectively forms pores on the hazelnut shell carbon to obtain a hazelnut shell-based porous carbon material with high specific surface area and large pore volume.

[0074] According to some further specific embodiments of the present application, the temperature of the above-mentioned activation pore-forming is 600°C to 800°C (for example, it can be 600°C, 650°C, 700°C, 750°C, 800°C, etc.), and the time is 30min to 70min (for example, it can be 30min, 40min, 50min, 60min, 70min, etc.). Therefore, by limiting the temperature and time of the above-mentioned activation pore-forming within the above-mentioned range, it can be further ensured that the activator effectively forms pores on the hazelnut shell carbon, thereby obtaining a hazelnut shell-based porous carbon material with a high specific surface area and a large pore volume.

[0075] According to some other specific embodiments of the present application, before grinding and mixing the hazelnut shell carbon and the activator, the method further includes: performing a second crushing on the hazelnut shell carbon to obtain hazelnut shell carbon powder, so as to facilitate sufficient grinding and mixing of the hazelnut shell carbon and the activator. Specifically, the hazelnut shell carbon can be secondly crushed by a ball mill.

[0076] As some specific embodiments, the target particle size of the sieve is no larger than 120 meshes, that is, the particle size of the crushed hazelnut shell carbon is no larger than 125 μm, which is further conducive to fully grinding and mixing the hazelnut shell carbon and the activator.

[0077] S300: acid-washing, water-washing and drying the activated and pore-forming material to obtain a hazelnut shell-based porous carbon material.

[0078] In this step, the material after activation and pore formation can be pickled with acid solution to neutralize the alkaline activator remaining in step S200; at the same time, during the pickling process, the metal element formed by the activator in the process of participating in the activation reaction can be washed away to retain the microporous structure; in addition, during the pickling process, the reactants formed by the alkali metal and alkaline earth metal in the process of participating in the activation reaction can also be washed away to form a microporous structure, thereby further improving the specific surface area and porosity of the hazelnut shell-based porous carbon material. The purpose of water washing is to wash away the acid solution remaining in the hazelnut shell-based porous carbon material after pickling.

[0079] According to some specific embodiments of the present application, the pickling time is 4h to 6h, for example, 4h, 4.5h, 5h, 5.5h, 6h, etc., thereby further ensuring that the alkaline activator remaining in step S200 is neutralized, and further ensuring that the metal element formed in the process of washing away the activator to participate in the activation reaction retains the microporous structure and the reactants formed in the process of washing away the alkali metal and alkaline earth metal to participate in the activation reaction form a microporous structure.

[0080] According to some further specific embodiments of the present application, water washing is performed until the pH value of the washing liquid is 7, thereby further ensuring that the acid liquid remaining in the hazelnut shell-based porous carbon material after acid washing is washed away.

[0081] According to some other specific embodiments of the present application, the acid solution includes at least one of hydrochloric acid (HCl) and nitric acid, and the acid solution can not only neutralize the alkaline activator remaining in step S200, but also wash away the metal element formed by the activator in the process of participating in the activation reaction, and the reactants formed by the alkali metal and alkaline earth metal in the process of participating in the activation reaction. Further, the concentration of the acid solution is 1mol / L to 3mol / L, for example, it can be 1mol / L, 1.5mol / L, 2mol / L, 2.5mol / L, 3mol / L, etc.

[0082] In the second aspect of the present application, a hazelnut shell-based porous adsorbent carbon material is proposed, and the hazelnut shell-based porous adsorbent carbon material is prepared by the method of the first aspect. As a result, the hazelnut shell-based porous adsorbent carbon material has a high specific surface area, high strength, and high pore volume, thereby effectively improving the adsorption performance and cyclic stability of the hazelnut shell-based porous adsorbent carbon material, so that the hazelnut shell-based porous adsorbent carbon material can be effectively used in the treatment of textile wastewater, papermaking wastewater or dye wastewater, especially in the treatment of methylene blue wastewater, to complete the removal of pollutants in wastewater.

[0083] According to some specific embodiments of the present application, the specific surface area of ​​the hazelnut shell-based porous adsorption carbon material is not less than 1000 m 2 / g, preferably 1300m 2 / g~3200m 2 / g, it can be seen that the hazelnut shell-based porous adsorption carbon material has a higher specific surface area.

[0084] According to some further specific embodiments of the present application, the micropore volume of the hazelnut shell-based porous adsorption carbon material is not less than 0.5 cm 3 / g, preferably 0.5cm 3 / g~1.2cm 3 / g, it can be seen that the hazelnut shell-based porous adsorption carbon material has a higher micropore volume.

[0085] According to some specific embodiments of the present application, the average pore size of the hazelnut shell-based porous adsorbent carbon material is not less than 1.5 nm, preferably 1.5 nm to 2.1 nm. It can be seen that the hazelnut shell-based porous adsorbent carbon material has a larger pore size.

[0086] In the third aspect of the present application, a hazelnut shell-based porous adsorbent carbon material prepared by the method described in the first aspect or the hazelnut shell-based porous adsorbent carbon material described in the second aspect is proposed for use in treating sewage. Thus, the hazelnut shell-based porous adsorbent carbon material can be effectively used in the treatment of textile sewage, papermaking sewage or dye sewage, and is particularly used in the treatment of methylene blue sewage to remove pollutants in sewage.

[0087] The embodiments of the present application are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. In addition, unless otherwise explicitly stated, all reagents used in the following embodiments are commercially available or can be synthesized according to this article or known methods, and the reaction conditions not listed are also easily available to those skilled in the art.

[0088] In Examples 1 to 9, the mass ratio of hazelnut shell carbon to activator (factor A), activation temperature (factor B) and activation time (factor C) were selected as three factors. Three data were taken for each factor within a reasonable range for experimental research. The orthogonal table L9 (3 3 ), complete 9 groups of experiments, namely Examples 1 to 9.

[0089] Embodiment 1:

[0090] This embodiment provides a method for preparing a hazelnut shell-based porous adsorbent carbon material, comprising:

[0091] First, the discarded hazelnut shells were cleaned, dried, and roughly crushed to a particle size of 2-3 mm. Then, they were sent to a muffle furnace for carbonization under a nitrogen atmosphere, with an initial temperature of 25 °C, a heating rate of 5 °C / min, a carbonization temperature of 550 °C, and a carbonization time of 2 h to obtain hazelnut shell carbon. The hazelnut shell carbon was crushed using a ball mill, passed through a 120-mesh sieve, and the hazelnut shell carbon powder of the target particle size was collected. Then, 4 g of hazelnut shell carbon powder was fully ground and mixed with KOH in a mass ratio of 1:1, and the mixture was placed in a tubular furnace for activation under a nitrogen atmosphere, with an initial temperature of 25 °C, a heating rate of 5 °C / min, an activation temperature of 600 °C, and an activation time of 30 min. After the activation was completed, the sample was taken out after the temperature dropped to room temperature. It was acid-washed with 100 mL of 2M HCl solution for 5 h. Then, the sample was filtered out using a vacuum filter and washed several times with deionized water until neutral. Finally, the sample was dried in a blast drying oven at 105 °C for 12 h to obtain hazelnut shell-based porous carbon 1.

[0092] Embodiment 2:

[0093] This embodiment provides a method for preparing a hazelnut shell-based porous adsorbent carbon material, comprising:

[0094] First, the waste hazelnut shells were cleaned, dried, and roughly crushed to a particle size of 2-3 mm. Then, they were sent to a muffle furnace for carbonization under a nitrogen atmosphere, with an initial temperature of 25 °C, a heating rate of 5 °C / min, a carbonization temperature of 550 °C, and a carbonization time of 2 h to obtain hazelnut shell carbon. The hazelnut shell carbon was crushed using a ball mill, passed through a 120-mesh sieve, and the hazelnut shell carbon powder of the target particle size was collected. Then, 4 g of hazelnut shell carbon powder was fully ground and mixed with KOH in a mass ratio of 1:1, and the mixture was placed in a tubular furnace for activation under a nitrogen atmosphere, with an initial temperature of 25 °C, a heating rate of 5 °C / min, an activation temperature of 700 °C, and an activation time of 50 min. After the activation was completed, the sample was taken out after the temperature dropped to room temperature. It was acid-washed with 100 mL of 2M HCl solution for 5 h. Then, the sample was filtered out using a vacuum filter and washed several times with deionized water until neutral. Finally, the sample was dried in a blast drying oven at 105 °C for 12 h to obtain hazelnut shell-based porous carbon 2.

[0095] Embodiment 3:

[0096] This embodiment provides a method for preparing a hazelnut shell-based porous adsorbent carbon material, comprising:

[0097] First, the waste hazelnut shells were cleaned, dried, and roughly crushed to a particle size of 2-3 mm. Then, they were sent to a muffle furnace for carbonization under a nitrogen atmosphere, with an initial temperature of 25 °C, a heating rate of 5 °C / min, a carbonization temperature of 550 °C, and a carbonization time of 2 h to obtain hazelnut shell carbon. The hazelnut shell carbon was crushed using a ball mill, passed through a 120-mesh sieve, and the hazelnut shell carbon powder of the target particle size was collected. Then, 4 g of hazelnut shell carbon powder was fully ground and mixed with KOH in a mass ratio of 1:1, and the mixture was placed in a tubular furnace for activation under a nitrogen atmosphere, with an initial temperature of 25 °C, a heating rate of 5 °C / min, an activation temperature of 800 °C, and an activation time of 70 min. After the activation was completed, the sample was taken out after the temperature dropped to room temperature. It was acid-washed with 100 mL of 2M HCl solution for 5 h. Then, the sample was filtered out using a vacuum filter and washed several times with deionized water until neutral. Finally, the sample was dried in a blast drying oven at 105 °C for 12 h to obtain hazelnut shell-based porous carbon 3.

[0098] Embodiment 4:

[0099] This embodiment provides a method for preparing a hazelnut shell-based porous adsorbent carbon material, comprising:

[0100] First, the discarded hazelnut shells were cleaned, dried, and roughly crushed to a particle size of 2-3 mm. Then, they were sent to a muffle furnace for carbonization under a nitrogen atmosphere, with an initial temperature of 25 °C, a heating rate of 5 °C / min, a carbonization temperature of 550 °C, and a carbonization time of 2 h to obtain hazelnut shell carbon. The hazelnut shell carbon was crushed using a ball mill, passed through a 120-mesh sieve, and the hazelnut shell carbon powder of the target particle size was collected. Then, 4 g of hazelnut shell carbon powder was fully ground and mixed with KOH in a mass ratio of 1:2, and the mixture was placed in a tubular furnace for activation under a nitrogen atmosphere, with an initial temperature of 25 °C, a heating rate of 5 °C / min, an activation temperature of 600 °C, and an activation time of 50 min. After the activation was completed, the sample was taken out after the temperature dropped to room temperature. It was acid-washed with 100 mL of 2M HCl solution for 5 h. Then, the sample was filtered out using a vacuum filter and washed several times with deionized water until neutral. Finally, the sample was dried in a blast drying oven at 105 °C for 12 h to obtain hazelnut shell-based porous carbon 4.

[0101] Embodiment 5:

[0102] This embodiment provides a method for preparing a hazelnut shell-based porous adsorbent carbon material, comprising:

[0103] First, the discarded hazelnut shells were cleaned, dried, and roughly crushed to a particle size of 2-3 mm. Then, they were sent to a muffle furnace for carbonization under a nitrogen atmosphere, with an initial temperature of 25 °C, a heating rate of 5 °C / min, a carbonization temperature of 550 °C, and a carbonization time of 2 h to obtain hazelnut shell carbon. The hazelnut shell carbon was crushed using a ball mill, passed through a 120-mesh sieve, and the hazelnut shell carbon powder of the target particle size was collected. Then, 4 g of hazelnut shell carbon powder was fully ground and mixed with KOH in a mass ratio of 1:2, and the mixture was placed in a tubular furnace for activation under a nitrogen atmosphere, with an initial temperature of 25 °C, a heating rate of 5 °C / min, an activation temperature of 700 °C, and an activation time of 70 min. After the activation was completed, the sample was taken out after the temperature dropped to room temperature. It was acid-washed with 100 mL of 2M HCl solution for 5 h. Then, the sample was filtered out using a vacuum filter and washed several times with deionized water until neutral. Finally, the sample was dried in a blast drying oven at 105 °C for 12 h to obtain hazelnut shell-based porous carbon 5.

[0104] Embodiment 6:

[0105] This embodiment provides a method for preparing a hazelnut shell-based porous adsorbent carbon material, comprising:

[0106] First, the discarded hazelnut shells were cleaned, dried, and roughly crushed to a particle size of 2-3 mm. Then, they were sent to a muffle furnace for carbonization under a nitrogen atmosphere, with an initial temperature of 25 °C, a heating rate of 5 °C / min, a carbonization temperature of 550 °C, and a carbonization time of 2 h to obtain hazelnut shell carbon. The hazelnut shell carbon was crushed using a ball mill, passed through a 120-mesh sieve, and the hazelnut shell carbon powder of the target particle size was collected. Then, 4 g of hazelnut shell carbon powder was fully ground and mixed with KOH in a mass ratio of 1:2, and the mixture was placed in a tubular furnace for activation under a nitrogen atmosphere, with an initial temperature of 25 °C, a heating rate of 5 °C / min, an activation temperature of 800 °C, and an activation time of 30 min. After the activation was completed, the sample was taken out after the temperature dropped to room temperature. It was acid-washed with 100 mL of 2M HCl solution for 5 h. Then, the sample was filtered out using a vacuum filter and washed several times with deionized water until neutral. Finally, the sample was dried in a blast drying oven at 105 °C for 12 h to obtain hazelnut shell-based porous carbon 6.

[0107] Embodiment 7:

[0108] This embodiment provides a method for preparing a hazelnut shell-based porous adsorbent carbon material, comprising:

[0109] First, the discarded hazelnut shells were cleaned, dried, and roughly crushed to a particle size of 2-3 mm. Then, they were sent to a muffle furnace for carbonization under a nitrogen atmosphere, with an initial temperature of 25 °C, a heating rate of 5 °C / min, a carbonization temperature of 550 °C, and a carbonization time of 2 h to obtain hazelnut shell carbon. The hazelnut shell carbon was crushed using a ball mill, passed through a 120-mesh sieve, and the hazelnut shell carbon powder of the target particle size was collected. Then, 4 g of hazelnut shell carbon powder was fully ground and mixed with KOH in a mass ratio of 1:3, and the mixture was placed in a tubular furnace for activation under a nitrogen atmosphere, with an initial temperature of 25 °C, a heating rate of 5 °C / min, an activation temperature of 600 °C, and an activation time of 70 min. After the activation was completed, the sample was taken out after the temperature dropped to room temperature. It was acid-washed with 100 mL of 2M HCl solution for 5 h. Then, the sample was filtered out using a vacuum filter and washed several times with deionized water until neutral. Finally, the sample was dried in a blast drying oven at 105 °C for 12 h to obtain hazelnut shell-based porous carbon 7.

[0110] Embodiment 8:

[0111] This embodiment provides a method for preparing a hazelnut shell-based porous adsorbent carbon material, comprising:

[0112] First, the waste hazelnut shells were cleaned, dried, and roughly crushed to a particle size of 2-3 mm. Then, they were sent to a muffle furnace for carbonization under a nitrogen atmosphere, with an initial temperature of 25 °C, a heating rate of 5 °C / min, a carbonization temperature of 550 °C, and a carbonization time of 2 h to obtain hazelnut shell carbon. The hazelnut shell carbon was crushed using a ball mill, passed through a 120-mesh sieve, and the hazelnut shell carbon powder of the target particle size was collected. Then, 4 g of hazelnut shell carbon powder was fully ground and mixed with KOH in a mass ratio of 1:3, and the mixture was placed in a tubular furnace for activation under a nitrogen atmosphere, with an initial temperature of 25 °C, a heating rate of 5 °C / min, an activation temperature of 700 °C, and an activation time of 30 min. After the activation was completed, the sample was taken out after the temperature dropped to room temperature. It was acid-washed with 100 mL of 2M HCl solution for 5 h. Then, the sample was filtered out using a vacuum filter and washed several times with deionized water until neutral. Finally, the sample was dried in a blast drying oven at 105 °C for 12 h to obtain hazelnut shell-based porous carbon 8.

[0113] Embodiment 9:

[0114] This embodiment provides a method for preparing a hazelnut shell-based porous adsorbent carbon material, comprising:

[0115] First, the discarded hazelnut shells were cleaned, dried, and roughly crushed to a particle size of 2-3 mm. Then, they were sent to a muffle furnace for carbonization under a nitrogen atmosphere, with an initial temperature of 25 °C, a heating rate of 5 °C / min, a carbonization temperature of 550 °C, and a carbonization time of 2 h to obtain hazelnut shell carbon. The hazelnut shell carbon was crushed using a ball mill, passed through a 120-mesh sieve, and the hazelnut shell carbon powder of the target particle size was collected. Then, 4 g of hazelnut shell carbon powder was fully ground and mixed with KOH in a mass ratio of 1:3, and the mixture was placed in a tubular furnace for activation under a nitrogen atmosphere, with an initial temperature of 25 °C, a heating rate of 5 °C / min, an activation temperature of 800 °C, and an activation time of 50 min. After the activation was completed, the sample was taken out after the temperature dropped to room temperature. It was acid-washed with 100 mL of 2M HCl solution for 5 h. Then, the sample was filtered out using a vacuum filter and washed several times with deionized water until neutral. Finally, the sample was dried in a blast drying oven at 105 °C for 12 h to obtain hazelnut shell-based porous carbon 9.

[0116] The preparation methods of Examples 1 to 9 are basically the same, and the differences are shown in Table 2.

[0117] Table 2

[0118]

[0119] Example 10

[0120] The preparation method of this embodiment is basically the same as that of embodiment 9, except that:

[0121] The carbonization temperature of the hazelnut shell in this embodiment is 600° C. Hazelnut shell-based porous carbon 10 is obtained.

[0122] Embodiment 11

[0123] The preparation method of this embodiment is basically the same as that of embodiment 9, except that:

[0124] The carbonization temperature of the hazelnut shell in this embodiment is 700° C. Hazelnut shell-based porous carbon 11 is obtained.

[0125] Example 12

[0126] The preparation method of this embodiment is basically the same as that of embodiment 9, except that:

[0127] The carbonization time of the hazelnut shell in this embodiment is 30 minutes to obtain the hazelnut shell-based porous carbon 12.

[0128] Example 13

[0129] The preparation method of this embodiment is basically the same as that of embodiment 9, except that:

[0130] The carbonization time of the hazelnut shell in this example is 3 hours to obtain the hazelnut shell-based porous carbon 13.

[0131] Comparative Example 1

[0132] In this comparative example, industrial lignin is used as a raw material and is modified by FeCl3 (ferric chloride) to obtain an industrial lignin-based carbon material. The maximum equilibrium adsorption capacity of the industrial lignin-based carbon material for methyl blue (MB) is 200.00 mg / g.

[0133] Comparative Example 2

[0134] In this comparative example, straw is used as raw material and a K2CO3 (potassium carbonate) chemical activation method is adopted to obtain a straw-based carbon material. The maximum equilibrium adsorption capacity of the straw-based carbon material for methyl blue (MB) is 274.84 mg / g.

[0135] Comparative Example 3

[0136] In this comparative example, peanut shells are used as raw materials, and nano Ce (cerium) is doped by an impregnation method to obtain a peanut shell-based carbon material. The maximum equilibrium adsorption capacity of the peanut shell-based carbon material for methyl blue (MB) is 270.27 mg / g.

[0137] Comparative Example 4

[0138] In this comparative example, tea residue is used as raw material, and FeCl3 (ferric chloride) and KOH (potassium hydroxide) chemical activation method are adopted to obtain tea residue-based carbon material, and the maximum equilibrium adsorption capacity of methyl blue (MB) of the tea residue-based carbon material is 394.30 mg / g.

[0139] The specific surface area and pore size distribution of the porous carbon of hazelnut shell prepared in Examples 1 to 13 were measured by physical adsorption instrument, wherein the specific surface area and pore size distribution were calculated using BET and DFT models, respectively, and the results are shown in Table 3. The adsorption isotherms of nitrogen adsorption and desorption of the porous carbon of hazelnut shell prepared in Examples 1 to 9 are shown in Table 3. Figure 2 As shown, the pore size distribution is Figure 3 shown.

[0140] The activation yield Y of the hazelnut shell porous carbon prepared in Examples 1 to 13 was calculated respectively, activation yield Y=mass of hazelnut shell carbon powder before activation / mass of hazelnut shell-based porous carbon obtained after activation acid washing, water washing and drying. The results are shown in Table 3.

[0141] Table 3

[0142]

[0143] From the attached Figures 2-3As can be seen from Table 3, the hazelnut shell porous carbon prepared in Examples 1 to 13 has a high specific surface area, high pore volume and high micropore volume, which is conducive to the storage of methylene blue molecules during the adsorption process; the average pore size is large, which facilitates the transmission of methylene blue molecules from the outer surface to the internal pores, thereby effectively improving the adsorption performance and cycle stability of the hazelnut shell-based porous adsorption carbon material. At the same time, it can be seen from Table 3 that the activation yield Y of the hazelnut shell porous carbon prepared in Examples 1 to 13 is relatively high.

[0144] The surface microstructure of the hazelnut shell raw material and the hazelnut shell porous carbon 9 of Example 9 was tested using a field emission scanning electron microscope. The test results are as follows: Figure 4 and Figure 5 The morphology of the hazelnut shell porous carbon 9 of Example 9 was tested using a field emission transmission electron microscope. The test results are shown in Figure 6 As shown. Figure 4 It can be seen that the pore structure of hazelnut shell raw materials is not well developed; Figure 5 and attached Figure 6 It can be seen that the activated hazelnut shell porous carbon 9 obtained in Example 9 not only has a rough outer surface with a rich pore structure, but also has abundant pore development inside and contains large cavities. Therefore, the hazelnut shell porous carbon 9 has a higher specific surface area. The micropores and mesopores of the sample are distributed in the macropore walls on the inner and outer surfaces, forming a pore structure with a well-developed pore structure. The rich micropores are conducive to providing adsorption sites and storage space for MB during the adsorption process, and the appropriate amount of mesopores and macropore structures provide convenient adsorption and transmission channels for MB molecules. Therefore, the porous carbon in Example 9 can show excellent performance in the application of adsorbing MB.

[0145] The hazelnut shell porous carbon prepared in Examples 1 to 13 was subjected to adsorption experiments on methylene blue (MB). The results are shown in the attached figure. Figure 7 As shown. The adsorption experiment of methylene blue (MB) by hazelnut shell-based porous carbon was carried out in a constant temperature water bath shaker. All adsorption experiments were carried out at room temperature. The initial concentration of methylene blue was 400 mg / L, the input amount of porous carbon was 10 mg, and the amount of MB was 30 mL. After adsorption equilibrium, the suspension was extracted with a syringe, and then a 0.45 μm polytetrafluoroethylene filter was used to obtain the adsorbed clear liquid. The absorbance of the MB solution was measured with a UV-visible spectrophotometer, and the concentration was calculated using the Beer-Lambert Law formula.

[0146] Attached Figure 7 The left ordinate of represents the adsorption amount of methylene blue (MB) when the adsorption of methylene blue (MB) by the porous carbon of hazelnut shell prepared in each embodiment reaches equilibrium. Figure 7The right ordinate of represents the removal rate of methylene blue (MB) when the adsorption of the porous carbon of hazelnut shell prepared in each embodiment reaches equilibrium, and the removal rate = the concentration of methylene blue when the adsorption reaches equilibrium / the initial concentration of methylene blue. Figure 7 It can be seen that compared with comparative examples 1 to 4, the hazelnut shell porous carbon of Examples 1 to 13 has a higher adsorption amount of methylene blue (MB) when the adsorption of methylene blue (MB) reaches equilibrium, and the removal rate of methylene blue is higher when the adsorption of methylene blue (MB) by the hazelnut shell porous carbon of Examples 1 to 13 reaches equilibrium. It can be seen that the hazelnut shell porous carbon prepared in Examples 1 to 13 has excellent adsorption performance.

[0147] The cyclic stability of the hazelnut shell porous carbon prepared in Example 9 for the adsorption of methylene blue solution was tested. The results are as follows: Figure 8 In the cyclic stability experiment, the initial concentration of methylene blue was 250 mg / L, the input amount of porous carbon was 10 mg, the amount of MB was 30 mL, and after the hazelnut shell porous carbon of Example 9 was saturated with adsorption, the porous carbon was filtered out and put into an appropriate amount of anhydrous ethanol solution for MB desorption. This step was repeated many times until the solution had no obvious color and then washed with deionized water several times, and then placed in a constant temperature oven at 105 degrees Celsius to dry to constant weight, and the adsorption process was repeated under the same adsorption conditions, and the adsorption process was repeated 5 times in total.

[0148] Attached Figure 8 The left ordinate of represents the adsorption amount of methylene blue (MB) when the adsorption of methylene blue (MB) by the porous carbon of hazelnut shell of Example 9 reaches equilibrium at each cycle number. Figure 8 The right ordinate of represents the removal rate of methylene blue (MB) when the adsorption of the porous carbon of hazelnut shell in Example 9 reaches equilibrium at each cycle number, and the removal rate = the concentration of methylene blue when the adsorption reaches equilibrium / the initial concentration of methylene blue. Figure 8 It can be seen that the hazelnut shell porous carbon of Example 9 still has a high adsorption capacity and removal rate for methylene blue (MB) after 5 cycles. It can be seen that the hazelnut shell porous carbon of the present application has excellent cycle performance.

[0149] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0150] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A method for preparing a hazelnut shell-based porous adsorbent carbon material, characterized in that: include: Pyrolysis and carbonization of hazelnut shells are performed to obtain hazelnut shell carbon; Grinding and mixing the hazelnut shell carbon and an activating agent to activate and form pores; The activated and pore-forming material is acid-washed, water-washed and dried to obtain a hazelnut shell-based porous carbon material.

2. The method according to claim 1, characterized in that: Before pyrolyzing and carbonizing the hazelnut shell, the method further comprises: Washing the hazelnut shells, drying them, and performing a first crushing; Optionally, washing the hazelnut shells with deionized water 3 to 5 times; Optionally, the average particle size of the hazelnut shells after the first crushing is 1 mm to 4 mm.

3. The method according to claim 1, characterized in that The hazelnut shell is subjected to pyrolysis carbonization under an inert atmosphere; And / or, the temperature for pyrolysis carbonization of the hazelnut shell is 550° C. to 700° C., and the time is 30 min to 3 h.

4. The method according to any one of claims 1 to 3, characterized in that Before grinding and mixing the hazelnut shell carbon with the activating agent, the method further comprises: performing a second crushing on the hazelnut shell carbon; Optionally, the particle size of the crushed hazelnut shell carbon is no more than 125 μm.

5. The method according to any one of claims 1 to 3, characterized in that: Activating and forming pores on the hazelnut shell carbon under an inert atmosphere; and / or, the activator comprises at least one of potassium hydroxide, sodium hydroxide, zinc chloride and potassium carbonate; and / or, the mass ratio of the hazelnut shell carbon to the activating agent is 1:(1-3); And / or, the activation pore-forming process is performed at a temperature of 600° C. to 800° C. and for a time of 30 min to 70 min.

6. The method according to any one of claims 1 to 3, characterized in that: Using acid solution to pickle the activated pore-forming material; And / or, the pickling time is 4h to 6h; And / or, the water washing is performed until the pH value of the washing liquid is 7.

7. The method according to claim 6, characterized in that The acid solution includes at least one of hydrochloric acid and nitric acid; And / or, the concentration of the acid solution is 1 mol / L to 3 mol / L.

8. A hazelnut shell-based porous adsorbent carbon material, characterized in that: The method according to any one of claims 1 to 7 is used to prepare the present invention.

9. The hazelnut shell-based porous adsorbent carbon material according to claim 8, characterized in that: The specific surface area of ​​the hazelnut shell-based porous adsorbent carbon material is not less than 1000 m 2 / g, preferably 1300m 2 / g~3200m 2 / g; And / or, the pore volume of the hazelnut shell-based porous adsorbent carbon material is not less than 0.5 cm 3 / g, preferably 0.5cm 3 / g~1.5cm 3 / g; And / or, the micropore volume of the hazelnut shell-based porous adsorbent carbon material is not less than 0.5 cm 3 / g, preferably 0.5cm 3 / g~1.2cm 3 / g; And / or, the average pore size of the hazelnut shell-based porous adsorbent carbon material is not less than 1.5 nm, preferably 1.5 nm to 2.1 nm.

10. Use of the hazelnut shell-based porous adsorbent carbon material prepared by the method according to any one of claims 1 to 7 or the hazelnut shell-based porous adsorbent carbon material according to claim 8 or 9 in treating sewage; Optionally, the hazelnut shell-based porous adsorption carbon material is used in treating textile wastewater, papermaking wastewater or dye wastewater.

Citation Information

Cited By

  • Cationic surface active agent modified porous carbon material as well as preparation and application thereof

    CN120550785A